Impact of Branched Chain Amino Acid on Muscle Mass, Muscle Strength, Physical Performance, Combined Survival, and Maintenance of Liver Function Changes in Laboratory and Prognostic Markers on Sarcopenic Patients With Liver Cirrhosis (BCAAS Study): A Randomized Clinical Trial - Singh Tejavath, Arun; Mathur, Amit; Nathiya, Deepak; Singh, Pratima; Raj, Preeti; Suman, Supriya; Mundada, Payal Ramakant; Atif, Sheikh; Rai, Ramesh Roop; Tomar, Balvir Singh (Frontiers in Nutrition, 2021)
Background: The study's primary objective was to investigate the long-term effect of Branched-chain amino acids supplementations on parameters associated with improved prognosis in sarcopenic patients with LC and evaluate its impact on cirrhotic-related events. Methods: We carried out a 24 week, single-centre, randomized, open-label, controlled, two cohort parallel-group intervention study comparing the efficacy of BCAA against lactoalbumin (L-ALB) on 106 sarcopenic liver cirrhotics. The BCAA (intervention) group was treated with 7.2 g BCAA per, whereas the lactoalbumin group was also given 6.3 g of L-Albumin. The primary outcome was to assess the impact of BCAA on parameters of sarcopenia: muscle mass, muscle strength, and physical performance. The secondary outcomes were to study combined survival and maintenance of liver function changes in laboratory and clinical markers in the duration of six months. Results: Treatment with BCAA leads to significant improvement in sarcopenic parameters: muscle strength, muscle function, and muscle mass. The total cirrhotic-related complications and cumulative event-free survival occurred fewer in the BCAA group than in the L-ALB group. Prognostic markers also improved significantly in the study. Conclusion: The current study demonstrated that long-term BCAAs supplementation improved sarcopenia and prognostic markers in patients with advanced liver cirrhosis.